9x-12=20-16x

Simple and best practice solution for 9x-12=20-16x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x-12=20-16x equation:


Simplifying
9x + -12 = 20 + -16x

Reorder the terms:
-12 + 9x = 20 + -16x

Solving
-12 + 9x = 20 + -16x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '16x' to each side of the equation.
-12 + 9x + 16x = 20 + -16x + 16x

Combine like terms: 9x + 16x = 25x
-12 + 25x = 20 + -16x + 16x

Combine like terms: -16x + 16x = 0
-12 + 25x = 20 + 0
-12 + 25x = 20

Add '12' to each side of the equation.
-12 + 12 + 25x = 20 + 12

Combine like terms: -12 + 12 = 0
0 + 25x = 20 + 12
25x = 20 + 12

Combine like terms: 20 + 12 = 32
25x = 32

Divide each side by '25'.
x = 1.28

Simplifying
x = 1.28

See similar equations:

| 19-9r=4-6r | | 112=16x | | 3x^2=-10x-5 | | 6-4x=7x+12 | | 18-2x=3x+8 | | 112=x-16 | | i^2+10i-24=0 | | 16=112x | | 93-6x=8x-23 | | 2(6x-1)+2(2x+5)=90 | | Z^3-5z+2=0 | | 3x^2+-17x+60=0 | | 10a+5(a-6)=66 | | 9x=x-40 | | x^2+6x-142=0 | | 36-2(x+2)=4x | | -12x^3+24x=0 | | 3x^2-17x+60=0 | | 5x+7=2x+11 | | -3x-5=7+7x | | 4x-(x-9)=42 | | -3(2+7n)=144 | | -10=-4x-13 | | S-57=38 | | 5-5x=12-4x | | 6(x+1)-8=6x-2 | | 12x+32=12-7 | | 6(9z-4)-[3(5z-2)+4]= | | -2(x+4)=0 | | x-4=-3x | | 5a-2a+9= | | 24=1i+.05i^2 |

Equations solver categories